New oleoyl hybrids of natural antioxidants: Synthesis and in vitro evaluation as inducers of apoptosis in colorectal cancer cells - Carullo, Gabriele; Mazzotta, Sarah; Koch, Anna Maria; Hartmann, Kristin; Friedrich, Oliver; Gilbert, Daniel; Vega-Holm, Margarita; Schneider-Stock, Regine; Aiello, Francesca (Antioxidants, 2020)
Nowadays, the beneficial role of a healthy lifestyle, particularly emphasizing the quality of foods and cancer management, is accepted worldwide. Polyphenols and oleic acid play a key role in this context, but are still scarcely used as anti-cancer agents due to their bio-accessibility limits. Therefore, we aimed to synthesize a set of new oleoyl-hybrids of quercetin, morin, pinocembrin, and catechin to overcome the low bioavailability of polyphenols, throughout a bio-catalytic approach using pancreatic porcine lipase as a catalyst. The in vitro assays, using a wide panel of human cancer cell lines showed, mainly for two novel regioisomer oleoyl-hybrids of quercetin, a remarkable increase in apoptotic cell populations. We suggested that the DNA damage shown as GH2AX signals might be the major cause of apoptotic cell death. Finally, we demonstrated convincing data about two novel polyphenol-based hybrids displaying a highly selective anti-cancer cytotoxicity and being superior compared to their reference/parental compounds.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Apoptosis; Colorectal cancer; Cytotoxicity; DNA damage; HCT-116; Oleic acid; Pancreatic porcine lipase; Polyphenol hybrids; Quercetin